Análisis del comportamiento de empresas peruanas y argentinas en su camino hacia un desempeño más sustentable - Morales-Alvarado, Lorenza (2022)
Currently, companies have been assuming the commitment to sustainability by adopting good practices of social responsibility with their stakeholders. Likewise, various international organizations promote initiatives that range from how and what considerations organizations should take into account when incorporating responsible practices in their value chain into their business strategies, to how to inform and render accounts to interested groups. This causes companies to disclose their performance on the management of their economic, social, environmental and governance impacts. The research focuses its objective on analyzing how companies have been integrating responsible initiatives in their information to be disclosed. The reports that the companies send to the Global Reporting Initiative (GRI) repository are used as the universe of analysis to determine the sample between representative Peruvian and Argentine companies. It is concluded that 100% of companies have been integrating the main initiatives of international organizations in their business strategies and reporting using the GRI methodology, however, 78% disclose in an essential and non-exhaustive manner, which implies that it is necessary that international organizations and countries aligned with sustainability strategies continue to encourage companies to adopt greater commitment and transparency in order to issue better quality performance reports for more efficient and effective communication with their stakeholders.